2013
DOI: 10.1159/000347017
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Patterns of Insulin-Like Growth Factor 2 in Human Uterine Fibroid Tissues: A Genetic Study with Clinical Correlations

Abstract: Background/Aims: We investigated insulin-like growth factor 2 (IGF-2) gene activity in human uterine fibroid tissue. Results of the genetic testing were correlated with clinical data. Methods: We obtained samples from patients treated for uterine fibroid and from patients undergoing hysterectomy due to other indications (control group). The examined group (with fibroid) contained 101 cases, while the control group was similar with 110 patients. Gene expression values were determined using the standard PCR tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The linked INS (insulin) and IGF-2 (insulin-like growth factor 2) genes emerged as putative targets in the present study but only in the EA population, consistent with the published data (27, 28). …”
Section: Discussionsupporting
confidence: 92%
“…The linked INS (insulin) and IGF-2 (insulin-like growth factor 2) genes emerged as putative targets in the present study but only in the EA population, consistent with the published data (27, 28). …”
Section: Discussionsupporting
confidence: 92%
“…Among them, deletions on 15q11.2-q23, 17p-q21.31, and 22q12.2-q12.3 had been reported previously, and deletions on 1q42.13, 11q13.1, and 13q12.13 were newly identified [15]. A recent study showed that the expression of the insulin-like growth factor 2 (IGF-2) gene, which is located on chromosome 11, was significantly higher in the ULM group [23]. Previous studies detected the same chromosomal alterations in extrauterine fibroids and ULM cells using aCGH [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact etiology of leiomyoma and its cystic degeneration is unknown [6,7], diffuse cystic degeneration is extremely rare, and the largest simple cystic degenerative uterine leiomyoma reported measured 10 cm [8]. To our knowledge, this is the largest case of cystic degeneration of a uterine leiomyoma yet reported.…”
Section: Discussionmentioning
confidence: 99%